P559 Incarceration, stress and sexual risk-taking: an intersectional analysis of black men who have sex with men in the deep south. (14th July 2019) - Callander, Denton; Duncan, Dustin; Park, Su Hyun; Bowleg, Lisa; Brinkley-Rubinstein, Lauren; Theall, Katherine; Hickson, Demarc
Abstract : Background: This study examined if the intersection of stress and experiences of incarceration was associated with sexual risk-taking among Black gay, bisexual and other men who have sex with men ('Black MSM') in the Deep South of the United States. Methods: Data for this analysis were collected during 2013–2015 as part of a study of sexual health among Black cisgender MSM in the states of Mississippi and Georgia. At baseline, participants responded to a 12-item scale of stressful experiences in the previous year with responses organized into tertiles (low, medium, high stress). Multivariate analyses assessed independent and interactional associations between stress/incarceration and several key sexual health risk practices. Results: Among our overall sample of 355 Black MSM, compared to those reporting a relatively low level of stress, a high level of stress was associated with drug use in the context of sex (adjusted odds ratio [OR]=2.0, 95% confidence interval [CI]:1.1–3.6, p=0.03). While this association was observed for men without incarceration histories (aOR=2.6, 95%CI:1.2–5.8, p=0.015), among those who had been incarcerated the relationship was stronger (aOR=3.9, 95%CI:1.8–8.6, p<0.001) and for these men experiencing even a medium level of stress was associated with sexual drug use (aOR=3.4, 95%CI:1.6–9.1, p<0.001). High stress among previously incarcerated MSM was also associated with condomless casual sex (aOR=2.8, 95%CI:1.3–6.1, p<0.001) and having ≥6 partners in six months (aOR=2.8, 95%CI:2.8-1.1-7.1, p=0.03); similar associations were not observed among men who had not been incarcerated. Conclusion: While stress was associated with some sexual risk taking among Black MSM, its intersection with incarceration was consistently (and more strongly) associated with a greater number and diversity of sexual risk practices. Men who have been incarcerated may struggle to deal with life stressors. Post-release programs for this population should provide adaptive tools for dealing with stress, including specific attention to safer sex and sexual risk. Disclosure: No significant relationships.